The Criminalisation of Unauthorised Immigrants: How Does Immigration Detention Become Punishment? - Albin, Tracy (Curtin University, 2017)
Asylum seekers and refugees are some of the most vulnerable people in the world. The sad reality is, they invite differing opinion towards them and are often considered as a burden to society. Despite having a structured and comprehensive international legal framework for the protection of these vulnerable people, many modern state practices fall short of the prescribed standards. On that backdrop, this paper focuses on the increasing convergence of criminal justice and immigration law, which has been colloquially named ‘crimmigration’, and is a recent topic of study for many scholars. It is argued by some writers that the practice of immigration detention is fundamentally modelled, and indeed operated, on the three fundamental principles of criminal justice: deterrence, retribution and punishment. This paper will demonstrate how different aspects of immigration detention reflect these principles, resulting in the criminalisation — and ultimately the punishment — of unauthorised immigrants in Australia, the United States and the United Kingdom.